2014
DOI: 10.1002/cjg2.20106
|View full text |Cite
|
Sign up to set email alerts
|

Features of Regional Variations of the Spontaneous Field

Abstract: According to the classification principle of field sources, the geoelectric field E is composed of the spontaneous field ESP and telluric field ET. The ESP originates from the physical and chemical actions of underground media. Its change and stability have usually obvious characteristics of local sites. The ET originates from the space current system and tidal forces, and shows the nature of broad areas in diurnal variation waveforms and spectral characteristics. In respect of the microscopic mechanism of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…On April 2, 1996 a moderate (M w 5.3) earthquake occurred very near to the fault with quasipure normal, E-W-striking focal mechanism (Kiratzi and Louvari, 2003; Figure 1b). The microseismic investigation of Tan et al (2014) revealed a cluster offshore of the central northern coast with a spatial distribution that depicts a N-dipping fault. This fault is also the candidate fault of the 2020 mainshock.…”
Section: The Western Anatoliamentioning
confidence: 99%
“…On April 2, 1996 a moderate (M w 5.3) earthquake occurred very near to the fault with quasipure normal, E-W-striking focal mechanism (Kiratzi and Louvari, 2003; Figure 1b). The microseismic investigation of Tan et al (2014) revealed a cluster offshore of the central northern coast with a spatial distribution that depicts a N-dipping fault. This fault is also the candidate fault of the 2020 mainshock.…”
Section: The Western Anatoliamentioning
confidence: 99%